Evolution of Lugosilesian orocline (north-eastern periphery of the Bohemian Massif): kinematics of Variscan deformation - Grygar,R.; Vavro,M. (Journal of the Czech Geological Society, 1995)
The north-eastern periphery of the Bohemian Massif was consolidated during long-lasting Variscan s.l. (Caledonian-Variscan) orogeny, in the conditions of the subequatorial oblique collision of more inner zones of the Variscan accretion wedge with the Brunovistulian terrane. This foreland corresponds to a mosaic of units most probably sutured, and jointly accreted, to the Baltica during the Caledonian orogeny. Regional kinematic analysis of the more internal domains (the Orlice-Sneznik Unit and its footwall envelope) proved the early-Variscan top-to-N lower crust synmetamorphic (higher rank of amphibolite to granulite-eclogite facies) nappe shearing. The Lower Devonian collision caused ENE-WSW transtensional stretching - oblique rifting of the Brunovistulian foreland brittle crust. The top-to-N thrusting of the Variscan orogenic front is recorded by an a-type of stretching lineations in the gneiss of the Orlice-Sneznik Unit. Due to the NW-SE trend of the western indented edge of the Brunovistulian foreland, an oblique dextral wrench collision in the Moravosilesian Zone occurred. The mentioned NNW-SSE transpressional shortening resulted in crustal overthickening and the top-to-SE back thrusting, especially in the Zabreh Unit and Silesicum. The late-Variscan transtension, with an ENE trend of stretching lineations, followed above mentioned crust overthickening. The gravitational collapse and out-ward lateral escape in the inner and deeper domains was contemporaneous with wide-spread intrusions of S-type granites and the growing of subperpendicular half-grabens, e.g. Boskovice and Orlice furrows. The dextral late-Variscan, and post-Variscan strike-slip kinematics along the Sudetic WNW trending transcurent faults resulted in a typical bend of orogen - the Lugosilesian orocline.
Keywords: Bohemian Massif; Moravosilesian Zone; oblique collision; transpression; transtension; crustal overthickening; crustal extension